Use of cardiac markers for monitoring of doxorubixin-induced cardiotoxicity in children with cancer - Yupada Pongprot (2018)
The aim of this study was to evaluate N-terminal probrain natriuretic peptides (NT-pro-BNP), cardiac troponin T, and creatinine kinase, MB isoenzyme (CK-MB) in the determination of subclinical left ventricular (LV) dysfunction by echocardiography in patients treated with doxorubicin. We performed a cross-sectional case study of systolic, diastolic function and tissue Doppler imaging by echocardiography in children with cancer who received a certain cumulative dose of doxorubicin. Blood levels for NT-pro-BNP, cardiac troponin T, and CK-MB were analyzed within 6 hours of the cardiac study. Of 30 patients, 5 (16.7%) had LV dysfunction with an abnormally high NT-pro-BNP level of 363±78 pg/mL, whereas patients with normal LV function had an NT-pro-BNP level of 148±173 pg/mL (P=0.012). The NT-pro-BNP level not only inversely correlated with fractional shortening (r=-0.43, P=0.017) and ejection fraction (r=-0.45, P=0.013) but also correlated with mitral deceleration time (r=0.41, P=0.021) and a cumulative dose of doxorubicin (r=0.44, P=0.014). For tissue Doppler imaging, NT-pro-BNP correlated with a peak systolic velocity at the myocardial segment (Sm) (r=-0.40, P=0.027). NT-pro-BNP is a sensitive test and has a moderate relationship with the LV systolic and diastolic function, thus making it a useful cardiac marker for the monitoring of early anthracycline cardiotoxicity. Copyright © 2012 by Lippincott Williams & Wilkins.